From Conflict to Peace? Stateness Assessment of the South Caucasus countries at the crossroads of political processes from 2017 to 2022 - Manukyan, Violetta (Journal of Political Science: Bulletin of Yerevan University, 2023)
The article reflects on the sustainability and security perspectives of the South Caucasus region. While discovering the different approaches to the notion of “stateness” and its assessment methodologies, the article brings up the problems of insufficient clarification of the concept, the need for further work on its conceptual and functional formulations. As the assessment also covers the non-recognized states, the peculiarities, difficulties and possibilities of stateness assessment of non-recognized states are revealed. The article proposes a definition of stateness and an integral model for stateness assessment, which would make it possible to carry out the stateness assessment of both recognized and non-recognized states within the framework of one model. With the help of the developed ‘Peace Index’, the article comprehensively assesses the levels of stateness of the three recognized: Armenia, Georgia and Azerbaijan; and the three non-recognized states of the South Caucasus: Nagorno-Karabakh, Abkhazia and South Ossetia through all four fields of stateness – political, economic, social and security for the years of 2017 to 2022. On the basis of the carried-out assessment, the article articulates policy recommendations for the South Caucasus countries and the region as a whole - guiding how to handle the current delicate situation in this strategically and geopolitically important region. The article suggests a) an immediate regional integration, b) economic cooperation as a key for conflict resolution, c) change of peace mediation format, d) support to the reconsideration of government-civil society relations format, making the civil societies of the South Caucasus states the inner constant peace-demanders and development-forcers - as the package-wise steps to transfer the South Caucasus region from conflict to peace.